Building an athletic brand : the University of South Carolina Beaufort crafts a new image - Nagel, Mark S.; McGee, Lynn W. (Lynn Wilson), 1955- (London : Human Kinetics, Inc., 2012)
In 2002, the state of South Carolina authorized the University of South Carolina Beaufort (USCB) to alter its role and mission from a two-year college to a four-year, baccalaureate-granting institution. As part of its desire to become a "full-service" university, USCB planned to begin intercollegiate athletic competition by 2007. In addition to launching the athletic department, USCB needed to select a mascot and logo that would be appropriate not only for the new athletic department, but also for the two-campus institution that was located in the beautiful South Carolina Sea Islands. Rather than simply have the chancellor or the new athletic director select the mascot and color scheme, USCB formed a mascot selection committee comprised of various on and off-campus stakeholders who utilized survey research to solicit a wide variety of potential mascot choices before undertaking its evaluations and making its final recommendation. This case provides details regarding USCB's mascot selection process and poses a variety of questions for students to contemplate when making athletic branding decisions.
Originally published in Nagel, M. S., & McGee, L. W. (2012). Building an athletic brand: The University of South Carolina Beaufort crafts a new image. Case Studies in Sport Management, 1(1), 59-75. DOI:.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; University of South Carolina at Beaufort -- Sports; Sports -- Marketing; Branding (Marketing)